2009
DOI: 10.1016/j.oraloncology.2009.05.562
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of CYP1A1 and CYP1B1 by benzo[a]pyrene in oral squamous cell carcinoma cell lines and by tobacco smoking in oral mucosa

Abstract: Polyaromatic hydrocarbons, including benzo[a]pyrene (BP), are major tobacco carcinogens. Their carcinogenic effects require metabolic activation by cytochrome p450 (CYP) enzymes. Relative CYP isoform expression is related to tissue-specific tobacco-related squamous cell carcinoma (SCC) susceptibility. There have been conflicting reports regarding relative CYP1A1 and CYP1B1 oral expression, and information regarding CYP1B1 expression in oral tissues is limited.OBJECTIVE-To quantify BP-and tobacco-induced CYP1A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Elevated CYP1A1 and CYP1B1 mRNA expression has been shown in extrahepatic tissues from smokers and in human cell lines treated with cigarette smoke condensate or the cigarette smoke component, benzo[a]pyrene (Buchthal et al, 1995;Chi et al, 2009;Hakkola et al, 1997;Iwanari et al, 2002;Nagaraj et al, 2006;Thum et al, 2006). In the current study, while no statistically significant differences were evident, a trend toward induction was observed for CYP1A1 (in PFC and AMG) and CYP1B1 (in AMG) in samples from smokers, with two AS individuals showing particularly high CYP1A1 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated CYP1A1 and CYP1B1 mRNA expression has been shown in extrahepatic tissues from smokers and in human cell lines treated with cigarette smoke condensate or the cigarette smoke component, benzo[a]pyrene (Buchthal et al, 1995;Chi et al, 2009;Hakkola et al, 1997;Iwanari et al, 2002;Nagaraj et al, 2006;Thum et al, 2006). In the current study, while no statistically significant differences were evident, a trend toward induction was observed for CYP1A1 (in PFC and AMG) and CYP1B1 (in AMG) in samples from smokers, with two AS individuals showing particularly high CYP1A1 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CYP2A6 and CYP2A13 are involved in the metabolic activation of tobacco-specific nitrosamines into reactive compounds that lead to liver and lungs toxicities [44]. Other tobacco constituents, such as polyarylhydrocarbons (PAH) are mainly activated by CYP1A1 and CYP1B1 [45, 46] that leads to the formation of recative metabolites, which has been shown to be associated with oral toxicity [46]. Furthermore, a study comprising 600 patients has demonstrated that CYP1A1 is a risk factor in oral cancer among smokers [45].…”
Section: Mechanism Of Tobacco Smoking Mediated Toxicity: Role Of Cypmentioning
confidence: 99%
“…For example, CYP1A1 mRNA levels are very high in the lung cells of smokers but typically undetectable in nonsmokers (15). CYP1A1 protein is also higher in smokers compared with nonsmokers (lung median levels of 16 versus 6.5 pmol/mg microsomal protein, respectively) (16), as well as in other tissues (17,18).…”
mentioning
confidence: 99%